2022
DOI: 10.1002/cssc.202201551
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field‐Assisted Construction and Enhancement of Electrocatalysts

Abstract: Driven by the energy crisis and environmental pollution, developing sustainable clean energy is an effective strategy to realize carbon neutrality. Electrocatalytic reactions are crucial to sustainable energy conversion and storage technologies, and advanced electrocatalysts are required to improve the sluggish electrocatalytic reactions. The magnetic field, as a thermodynamic parameter independent of temperature and pressure, is vital in the construction of electrocatalysts and enhancement of electrocatalysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 152 publications
(321 reference statements)
0
10
0
Order By: Relevance
“…158 While there has been considerable interest in the magnetic field-driven enhancement of the OER in spinel oxides in recent years, the majority of research has focused on spin dynamics. 159,160 Lyu 161 has presented the first strategy for manipulating the tetrahedral units in NiFe 2 O 4 (NFO) using magnetic fields to improve OER performance. Through their research, they found that the application of a magnetic field can cause Ni 2+ ions to migrate from the octahedral ( O h ) site to the tetrahedral ( T d ) site in mixed NFO spinels (Fig.…”
Section: Magnetic Field-enhanced Electrocatalysismentioning
confidence: 99%
“…158 While there has been considerable interest in the magnetic field-driven enhancement of the OER in spinel oxides in recent years, the majority of research has focused on spin dynamics. 159,160 Lyu 161 has presented the first strategy for manipulating the tetrahedral units in NiFe 2 O 4 (NFO) using magnetic fields to improve OER performance. Through their research, they found that the application of a magnetic field can cause Ni 2+ ions to migrate from the octahedral ( O h ) site to the tetrahedral ( T d ) site in mixed NFO spinels (Fig.…”
Section: Magnetic Field-enhanced Electrocatalysismentioning
confidence: 99%
“…By means of permanent magnets, incorporating an external MF is another representative noncontact energy transfer method to memorably impact the electrocatalytic proprieties by MF‐induced effects, such as spin polarization and spin‐selective effect. [ 81–85 ] Additionally, the Lorentz force (trueF $\vec{F}$) can directly act on targeted ions in convective flow to regulate their motion behaviors for enhanced mass transfer or optimal redistribution. [ 37,86–88 ] Other magnetic hyperthermia effects caused by alternating MF may lead to localized intense heating, also facilitating electrochemical reactions.…”
Section: Comparison Of Various Field‐assisted Electrocatalysismentioning
confidence: 99%
“…The additional clean energy input by introducing physical fields such as light and electricity is provided to reduce the energy barrier between reactants and products and accelerate the chemical reactions. [10][11][12] In view of the above two problems, magnetic field, with the non-contact and environmentally friendly nature, attracts increasing attention as an emerging method for providing new and lasting power for CO 2 capture and conversion. [13,14] CO 2 is a typical quadrupole molecule and its adsorption is supposed to be affected by the external field.…”
Section: Introductionmentioning
confidence: 99%